Treatment of Whiplash-Associated Disorders - Part I: Non-Invasive Interventions. (1st March 2005) - Conlin, Anne; Teasell, Robert; Bhogal, Sanjit; Sequeira, Keith
Abstract : BACKGROUND: A whiplash-associated disorder (WAD) is an injury due to an acceleration-deceleration mechanism at the neck. WAD represents a very common and costly condition, both economically and socially. In 1995, the Quebec Task Force published a report that contained evidence-based recommendations regarding the treatment of WAD based on studies completed before 1993 and consensus-based recommendations. OBJECTIVE: The objective of the present article - the first installment of a two-part series on interventions for WAD - is to provide a systematic review of the literature published between January 1993 and July 2003 on noninvasive interventions for WAD using meta-analytical techniques. METHODS OF THE REVIEW: Three medical literature databases were searched for identification of all studies on the treatment of WAD. Randomized controlled trials (RCTs) and epidemiological studies were categorized by treatment modality and analyzed by outcome measure. The methodological quality of the RCTs was assessed. When possible, pooled analyses of the RCTs were completed for meta-analyses of the data. The results of all the studies were compiled and systematically reviewed. RESULTS: Studies were categorized as exercise alone, multimodal intervention with exercise, mobilization, strength training, pulsed magnetic field treatment and chiropractic manipulation. A total of eight RCTs and 10 non-RCTs were evaluated. The mean score of methodological quality of the RCTs was five out of 10. Pooled analyses were completed across all treatment modalities and outcome measures. The outcomes of each study were summarized in tables. CONCLUSIONS: There exists consistent evidence (published in two RCTs) in support of mobilization as an effective noninvasive intervention for acute WAD. Two RCTs also reported consistent evidence that exercise alone does not improve range of motion in patients with acute WAD. One RCT reported improvements in pain and range of motion in patients with WAD of undefined duration who underwent pulsed electromagnetic field treatment. Conflicting evidence in two RCTs exists regarding the effectiveness of multimodal intervention with exercise. Limited evidence, in the form of three non-RCTs, exists in support of chiropractic manipulation. Future research should be directed toward clarifying the role of exercise and manipulation in the treatment of WAD, and supporting or refuting the benefit of pulsed electromagnetic field treatment. Mobilization is recommended for the treatment of pain and compromised cervical range of motion in the acute WAD patient.